Current Pharmacological Strategies for Duchenne Muscular Dystrophy - Yao, Shanshan; Chen, Zihao; Yu, Yuanyuan; Zhang, Ning; Jiang, Hewen; Zhang, Ge; Zhang, Zongkang; Zhang, Baoting (Frontiers in Cell and Developmental Biology, 2021)
Duchenne muscular dystrophy (DMD) is a lethal, X-linked neuromuscular disorder caused by the absence of dystrophin protein, which is essential for muscle fiber integrity. Loss of dystrophin protein leads to recurrent myofiber damage, chronic inflammation, progressive fibrosis, and dysfunction of muscle stem cells. Even though great endeavor was devoted to developing an effective therapy, there is still no cure for DMD so far. The therapeutic strategies are mainly divided into two lines. Dystrophin-targeted therapeutic strategies that aim at restoring the expression and/or function of dystrophin. The other line of therapeutic strategies aims to improve muscle function and quality by targeting the downstream pathological mechanisms. This review introduces the important developments in these two lines of strategies, especially those that have entered the clinical phase and/or have great potential for clinical translation. The rationale and efficacy of each agent in preclinical or clinical studies are presented. Furthermore, a meta-analysis of gene profiling in DMD patients was performed to understand the molecular mechanisms of DMD.